2023
DOI: 10.1159/000529550
|View full text |Cite
|
Sign up to set email alerts
|

Skin Care in Neonates and Infants: A Scoping Review

Abstract: Background Skin care is a basic, daily activity performed by formal and informal caregivers from birth until end of life. Skin care activities are influenced by different factors as e.g., culture, knowledge, industrial developments and marketing activities. Therefore, various preferences, traditions and behaviours exist worldwide including skin care of neonates and infants. Objective of this scoping review was to obtain an overview about the evidence of skin care activities in neonates and infants. Studies fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…However, the authors demonstrated the most significant increase in alkaline soap (+0.453) compared to the other groups [26]. Recently, a scoping review of neonatal skin care concluded that cleansing was one of the interventions with the most evidence and pointed out the impact of all cleansing products on moisturizing and skin pH, mainly that exposure to alkaline soaps could impact the skin barrier, produce irritation, and cause pathogenic colonization [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors demonstrated the most significant increase in alkaline soap (+0.453) compared to the other groups [26]. Recently, a scoping review of neonatal skin care concluded that cleansing was one of the interventions with the most evidence and pointed out the impact of all cleansing products on moisturizing and skin pH, mainly that exposure to alkaline soaps could impact the skin barrier, produce irritation, and cause pathogenic colonization [27].…”
Section: Discussionmentioning
confidence: 99%
“…The reviews covered the effect of topical oils on neonatal skin, 23 effect of skin care practices on healthy term babies' skin, 24 and a scoping review on skin care in neonates and infants. 6 The systematic review of topical oils (n=5683, mostly preterm infants) reported 11 of 14 studies were of moderate quality and found topical oils (sunflower (8), coconut (5), almond (2), olive (1), mustard (1), vegetable (1)) improved skin condition and barrier function of skin compared to 'standard care' or 'no oil application' groups.…”
Section: Cleansers Moisturisers and Skin Barrier Productsmentioning
confidence: 99%
“…Many outcome domains were found ( 57), e.g., dryness, erythema, nappy/diaper dermatitis, oedema, excoriation, trans epidermal water loss (TEWL) and overall skin condition. 6 Eight RCTs investigated topical oils, baby cleansing wipes, timing of bathing, or timing of moisturising. Of these, five RCTs, (four with preterm infants, ranging from 72−995 participants) of sunflower seed oil, almond oil, liquid Vaseline, coconut oil, or a general moisturiser, all found improved skin hydration and condition or pH compared to the control groups.…”
Section: Cleansers Moisturisers and Skin Barrier Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…(9,19-21-) It was developed by the researchers and used to assess nurses' practice regarding neonates ' skin care after reviewing recent related literatures. (22)(23)(24)(25)(26)(27)(28)…”
Section: Tools Of Data Collection: Two Tools Were Used To Collect The...mentioning
confidence: 99%